Employing a sequential multiple assignment randomized trial (SMART) to evaluate the impact of brief risk and protective factor prevention interventions for American Indian Youth Suicide - O’Keefe, Victoria M. (BMC Public Health, 2019)
BACKGROUND: This study is built on a long-standing research partnership between the Johns Hopkins Center for American Indian Health and the White Mountain Apache Tribe to identify effective interventions to prevent suicide and promote resilience among American Indian (AI) youth. The work is founded on a tribally-mandated, community-based suicide surveillance system with case management by local community mental health specialists (CMHSs) who strive to connect at-risk youth to treatment and brief, adjunctive interventions piloted in past research. METHODS: Our primary aim is to evaluate which brief interventions, alone or in combination, have the greater effect on suicide ideation (primary outcome) and resilience (secondary outcome) among AI youth ages 10–24 ascertained for suicide-related behaviors by the tribal surveillance system. We are using a Sequential Multiple Assignment Randomized Trial with stratified assignment based on age and suicidal-behavior type, and randomizing N = 304 youth. Brief interventions are delivered by AI CMHSs, or by Elders with CMHS support, and include: 1) New Hope, an evidence-based intervention to reduce immediate suicide risk through safety planning, emotion regulation skills, and facilitated care connections; and 2) Elders’ Resilience, a culturally-grounded intervention to promote resilience through connectedness, self-esteem and cultural identity/values. The control condition is Optimized Case Management, which all study participants receive. We hypothesize that youth who receive: a) New Hope vs. Optimized Case Management will have significant reductions in suicide ideation; b) Elders’ Resilience vs. Optimized Case Management will have significant gains in resilience; c) New Hope followed by Elders’ Resilience will have the largest improvements on suicide ideation and resilience; and d) Optimized Case Management will have the weakest effects of all groups. Our secondary aim will examine mediators and moderators of treatment effectiveness and sequencing. DISCUSSION: Due to heterogeneity of suicide risk/protective factors among AI youth, not all youth require the same types of interventions. Generating evidence for what works, when it works, and for whom is paramount to AI youth suicide prevention efforts, where rates are currently high and resources are limited. Employing Native paraprofessionals is a means of task-shifting psychoeducation, culturally competent patient support and continuity of care. TRIAL REGISTRATION: Clinical Trials NCT03543865, June 1, 2018.